“An Overwhelming Cloud of Inertia”: Evaluating the Impact of Course Design Changes Following the COVID-19 Pandemic - Joann S. Olson; Rita Kenahan (Online Learning, 2021)
In the wake of the COVID-19 pandemic, beginning in March 2020, educators at all levels faced the challenge of responding to student needs and utilizing technology for instruction. While much of the emerging research highlights the experiences of students and instructors as they shifted from face-to-face to remote learning, this study explores the experiences of students in a fully online graduate program as the scope of the pandemic was growing. What is the best way to maintain a community of inquiry (Garrison et al., 2000) when so much is changing? This case study explores the impact of a variety of course design changes that sought to help students meet learning objectives while also seeking to alleviate the unanticipated pressures created by external forces. Ultimately, the findings suggest that increased flexibility with due dates and access to course materials were the most helpful strategy for helping students deal with the disruptive events of the semester. In addition, managing the disruptions and finding some sense of balance were important for both instructors and students.